Chemical equilibrium and kinetic study of the esterification of pure and deluted acrylic acid with 2 ethyl hexanol catalysed by amberlyst 15 - Mohd Amirul Asyraf, Ahmad (2014)
In a typical acrylic manufacturing unit, waste water contains acrylic acid (AA) in a range of 4-15 wt% contributes to the high value of chemical oxygen demand. Due to the toxicity of AA to the aquatic organism, this wastewater should be treated before it is discharged. Recovery of AA from the waste water via esterification reaction in a reactive distillation column (RDC) could be a promising method to treat this waste water. Activity and kinetic studies using a batch system are important to examine the 'practicability of this method. In the present work, the activity and kinetic studies of the esterification of AA and 2-ethyl hexanol (2EH) were carried out in a batch system. Ion exchange resin, Amberlyst 15 was employed as a catalyst. The effect of various variables that affecting conversion and yield such as agitation speed, catalyst particle size, temperature, catalyst loading and initial reactant molar ratio were studied. The effect of the initial water content was studied using both the batch systems with total reflux (TR) and dean stark for continuously water removal (CWR). The increase of equilibrium conversion with the temperature indicated the endothermicity of the reaction. Temperature was the most significant variable that affected the conversion and yield. The highest conversion and yield were obtained at the temperature of 388 K, initial reactant molar ratio of AA to 2EH of 1:3 and catalyst loading of 10 wt%. The yield for the reactions of the AA solutions with different AA concentrations except the AA concentrations of 10-20 wt%, was enhanced significantly when the reactions were carried out using the CWR setup. Catalyst poisoning occurred during the reactions of the very dilute AA solutions (10-20%) due to the water inhibition and poly-acrylic acid deposition on the catalyst surface as validated by the catalyst characterisation studies. The pseudo-homogeneous (PH), Eley-Rideal (ER) and Langmuir-HinshelwoodHougen-Watson (LHHW) kinetic models were used to interpret the kinetic data. The best fit kinetic model for the main esterification reaction was shown by the non-ideal ER model while the side reaction, AA polymerisation was best interpreted by PH model. The kinetic data for the esterification of dilute AA was well described by the inclusion of the correction factor to the kinetic model of the esterification.